An Experimental Study of the Unsteady Aerodynamics of a Static DU91‐W2‐150 Airfoil at Large Angles of Attack - Guanqun Xu; Wei Yu; Andrea Sciacchitano; Carlos Simao Ferreira (Wind Energy)
ABSTRACT The airfoil DU91‐W2‐150 was investigated in the Low Speed Low Turbulence Tunnel at the Delft University of Technology to study unsteady aerodynamics. This experimental study tested the airfoil under a wide range of angles of attack (AoA) from 0° to 310° at three Reynolds numbers (Re) from 2×105 to 8×105. Pressure on the airfoil surface was measured and particle image velocimetry (PIV) measurements were conducted to capture the flow field in the wake. By examining the force coefficient and comparing the wake contours, it shows that an upwind concave surface provides a higher load compared to a convex surface upwind case, highlighting the critical role of surface shape in aerodynamics. When comparing separation at specific locations along the chord for all three Re values, it is observed that as Re increases, separation tends to occur at lower AoA, both for positive stall and negative stall. The examination of the aerodynamic force variation indicates that, during reverse flow, fluctuations are more pronounced compared to forward flow. This is owing to separation occurring at the aerodynamic leading edge (geometric trailing edge) in reverse flow. In terms of vortex shedding frequency, the study found a nearly constant normalized Strouhal number (St) of 0.16 across various Re and AoA values in fully separated regions, indicating a consistent pattern under these conditions. However, a slight increase in St, between 0.16 and 0.20, was observed for AoA values exceeding 180°, possibly due to the convex curvature of the airfoil in the upwind direction. In conclusion, this research not only corroborates previous findings for small AoA values but also adds new data on the aerodynamic behavior of the DU91‐W2‐150 airfoil under large AoA values, offering various perspectives on the effects of surface curvature, Re, and flow conditions on key aerodynamic parameters.